Pengaruh Work-Life Balance dan Disiplin Kerja terhadap Kinerja Pegawai Dinas Perhubungan Kota Depok - Urmila Tri Cahyani; Taat Kuspriyono; Yunidyawati Azlina (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study is based on the importance of maintaining a balance between work and personal life, as well as discipline, in supporting employee performance—particularly in the public sector. The objective of this research is to analyze the influence of work-life balance and work discipline on the performance of employees at the Department of Transportation in Depok City. A quantitative approach was used, employing a survey method. Data were collected through questionnaires distributed to 51 respondents and analyzed using multiple linear regression with the assistance of SPSS 26 software.The results indicate that the work-life balance variable (X1) significantly influences employee performance, as evidenced by a t-value of 3.787 > t-table value of 2.011 and a significance level of 0.000 < 0.05. In contrast, the work discipline variable (X2) does not have a significant partial effect, as shown by a t-value of 0.271 < t-table and a significance level of 0.787 > 0.05. However, simultaneously, both variables significantly influence employee performance, as shown by an F-value of 7.685 > F-table and a significance level of 0.001 < 0.05. The results of the coefficient of determination test show an R Square value of 0.243. This indicates that work-life balance (X1) and work discipline (X2) collectively explain 24.3% of the variation in employee performance (Y), while the remaining 75.7% is influenced by other factors beyond the scope of this study.